Improving the processes of cost management in the construction and energy projects - Babaev, Vladimir; Sukhonos, Maria; Starostina, Alona; Beletsky, Igor (Eastern-European Journal of Enterprise Technologies, 2016)
The processes of the cost management of construction-energy projects were improved by expanding the existing set of tools of project management by the method of planning the cost of construction-energy projects. The basis for developing the method is a hypothesis about specific features of the given projects being their structural complexity, significant resource intensity and duration, as well as a large number of stakeholders. This leads to a change in the costs of resources in the period of implementation of the project, and consequently, creates deviations towards its increase over its planned budget. These deviations can be forecasted and considered by using the developed method of planning the cost of construction- energy projects. This method, in contrast to the existing ones, is based on the theory of changeability in the costs of resources over time and it also considers investment and time constraints of the project. A verification of the proposed method was conducted, it was revealed that its results are more realistic, i.e., they are more in line with the actual data than the results, obtained by application of classical methods of planning the cost of projects. The developed method of planning the cost of construction-energy projects can be used for the projects in different directions provided they are long-term and expensive resources comprise a considerable share of their budget.